Kadrovski management v sodobni organizaciji (University of Maribor Press, 2017)
Human Resource Management in Modern Organization. This monographfocuses on some of the key issues of human resource management. Personnel planning, internal communication, careers, education and training, crisis management, and challenges in employment in the 21st century are discussed. The introductory paper illustrates the influence of the Fourth Industrial Revolution on the strategic planning of human resources in organizations. Following this, the internal communication and the results of a survey on which contents the employees are particularly interested in are shown. Many employees face the problem of transition from one career to another. Thus, an example of a career transition of top athletes is presented. The implementation of the strategic personnel planning is also conditioned by educational processes. The use of a new concept in education, the so-called gamification, is also presented. Continuous social changes and changes in technology bring advancement of civilization, yet at the same time they increase the likelihood of crises. The authors therefore emphasize the important role of crisis management. Finally, the changes in the labour market,which along with the new economy, global business and new forms of work influence the development concepts of organizations, the individual and the entire society, are presented.